Експериментальне вивчення бортництва у Північній експедиції. Сучасний промисел та його дослідне відтворення - Готун, І.А.; Коваль, О.А.; Петраускас, А.В. (Інститут археології НАН України, 2009)
Другу частину статті про середньовічне бортництво присвячено особливостям виготовлення бортей, поселенню роїв на базі експедиції — у регіоні традиційного бджолярства — та аналізу архаїчних форм цього промислу в Житомирському Поліссі. Вторая часть работы по экспериментальному воссозданию средневекового бортничества в Северной экспедиции Института археологии НАН Украины посвящена описанию архаического и современного бортничества на Житомирщине и опытам в этой отрасли на базе экспедиции между селами Ходосовка и Лесники. Охарактеризованы особенности технологий и приспособлений, применяемых современными бортниками, а также существенные моменты их практики. Привлечение документов XVIII—XIX вв. позволило проследить развитие промысла в регионе работы экспедиции и благодаря этому проводить опыты в более тесной связи со спецификой исследуемого поселения и его округи. Описаны последовательность эксперимента, необходимый инструментарий — от процесса производства бортей до поселения пчелиных семей и изготовления питьевого меда, широко упоминаемого письменными источниками средневековья. The second part of the article on experimental reconstruction of medieaval apiculture by the Northern Expedition of the Institute of Archaeology of the Academy of Sciences of Ukraine describes archaic and modern beekeeping in Zhytomyr region as well as experiments in this field on the basis of the Expedition between the villages of Khodosivka and Lisnyky. Specifics of technologies and devices used by modern bee-keepers are characterized and the important aspects and practices are analysed. Analysis of documents of the 18th—19th centuries allows the authors to trace the development of beekeeping in the region of the Expedition’s activity, which enabled them to conduct experiments in a closer connection with the specifics of the settlement under research and of its vicinity. A description of the experiment sequence and of the necessary tools is provided, starting from the process of hives making to hiving swarms of bees and production of honey beverage, which was broadly mentioned in medieaval written sources.